Nutraceutical Potential of Encapsulated Purple Okra (Abelmoschus Esculentus L. Moench) Extract - Salsabila, Dhea Marliana; Damayanthi, Evy; Nasution, Zuraidah (Universitas Airlangga, 2023)
The accumulation of free radical production impacts on the development of degenerative diseases which are the highest cause of morbidity and mortality in the world. Biofortification of purple okra in the form of encapsulated extract has the potential as a nutraceutical through the role of antioxidants. This study aimed to analyze the potential of encapsulated purple okra extract as a nutraceutical by determining physical-chemical characteristics, microbial and heavy metals contamination, antioxidant capacity, total flavonoids, and quercetin. This was a laboratory experimental study on purple okra which was extracted using the maceration method. The results of physical-chemical characteristics showed that purple okra extract has the form of dry powder, greenish-brown color, odor characteristic of okra extract (caramel-like), and sour taste with yield of 4%, pH of 4.8, undetectable solvent residue, water content of 13.5%, total ash content of 10.4%, and disintegration time of 1.25 minutes. The results of microbial contamination showed a total plate count of 3.1 102 CFU g⻹, yeast and mold count, E. coli, S. aureus negative CFU g⻹, and Salmonella spp negative CFU 10g⻹. The results of heavy metal contamination showed that As, Pb, Cd, and Hg were not detected every mg Kg⻹. The results of antioxidant capacity, total flavonoids, and suspected quercetin derivatives showed a value of 84.88%, 81.32 mg QE g⻹, and 4.91 mg g⻹. These bioactive components act as free radical scavengers in helping to prevent chain reactions. Encapsulated purple okra extract has shown its potential as a nutraceutical that helps prevent degenerative diseases.